Open Questions in the Management of Nodular Lymphocyte Predominant Hodgkin Lymphoma - Marguerite Tyran; Laurence Gonzague; Reda Bouabdallah; Michel Resbeut (Case Reports in Hematology)
Localized Nodular Lymphocyte Predominant Hodgkin Lymphoma is a rare disease with an overall good prognosis but frequent late relapses. Due to it’s rarity there is no standard therapeutic approach and pathological diagnosis may be hard. In this paper we discuss the technical aspects of the radiation therapy and histological issues. The new fields reductions proposed for classical Hodgkin lymphoma cannot be applied to early stages Nodular Lymphocyte Predominant Hodgkin lymphomas which are usually treated with radiation therapy without systemic chemotherapy.